A Systematic Review of Predictors of Reintervention After EVAR: Guidance for Risk-Stratified Surveillance. (August 2017) - Patel, Shaneel R.; Allen, Chris; Grima, Matthew J.; Brownrigg, Jack R. W.; Patterson, Benjamin O.; Holt, Peter J. E.; Thompson, Matt M.; Karthikesalingam, Alan
Background: Current surveillance protocols after endovascular aneurysm repair (EVAR) are ineffective and costly. Stratifying surveillance by individual risk of reintervention requires an understanding of the factors involved in developing post-EVAR complications. This systematic review assessed risk factors for reintervention after EVAR and proposals for stratified surveillance. Methods: A systematic search according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines was performed using EMBASE and MEDLINE databases to identify studies reporting on risk factors predicting reintervention after EVAR and proposals for stratified surveillance. Results: Twenty-nine studies reporting on 39 898 patients met the primary inclusion criteria for reporting predictors of reintervention or aortic complications with or without suggestions for stratified surveillance. Five secondary studies described external validation of risk scores for reintervention or aortic complications. There was great heterogeneity in reporting risk factors identified at the pre-EVAR, intraoperative, and post-EVAR stages of treatment, although large preoperative abdominal aortic aneurysm diameter was the most commonly observed risk factor for reintervention after EVAR. Conclusion: Existing data on predictors of post-EVAR complications are generally of poor quality and largely derived from retrospective studies. Few studies describing suggestions for stratified surveillance have been subjected to external validation. There is a need to refine risk prediction for EVAR failure and to conduct prospective comparative studies of personalized surveillance with standard practice.